Effectiveness of Moringa oleifera and PAC (Poly Aluminum Cloride) Leaves in Peat Organic Substances in Rasau Jaya Village, Kubu Raya Regency - Ratnawaty, Gervacia Jenny; Salim, Maulidiyah (Politeknik Negeri Ujung Pandang, 2021)
One source of surface water in West Kalimantan is peat water that has low turbidity, dark brown to black (124 - 850 units of PtCo), high organic content (138-1560 mg / L KMnO4), and is acidic (pH 3,7 - 5,3). The purpose of this study was to determine the effect of the addition of PAC and Moringa oleifera leaves to the decrease in levels of peat organic water in the Rasau Jaya village area, Kubu Raya Regency. The method used in this research is by mixing Moringa leaf powder and PAC (Poly Aluminum Cloride) in peat water accompanied by stirring and precipitating. Furthermore, peat water samples were analyzed for their organic content using the permanganometric titration method. The results showed that the levels of organic substances in peat water before the addition of PAC and Moringa leaf powder amounted to 176.96 mg / l, after the addition of 125 mg PAC and Moringa leaf powder with concentrations of 25, 50, 75 l , 100, 125, 150, 175, 200 mg/l, respectively: 42.04 mg / l, 46.97 mg / l, 58.14 mg / l, 66.15 mg / l, 67.20 mg / l, 60.25 mg / l, 63.41 mg / l, and 53.07 mg / l. Based on the results through regression statistical tests obtained sig = 0.015 <0.05 which means Ha is accepted that there is an effect of increasing the concentration of Moringa oleifera powder and PACÂ on Organic Content in Peat Water in Rasau Jaya Village, Kubu Raya Regency.